(untitled) (Fiep Bulletin - online, 2011)
The objective of this study was to analyze the training loads used by the Physical Coaches or Trainers for the development of the futsal athletes’ physical preparation sub-20 that disputed the championship amazonense in 2009. The sample was composed by five physical coaches of the teams. The results were obtained through the application of a questionnaire with fifteen open and closed subjects done in a direct way, among the days 08/10 to 13/10. The results demonstrated that there is knowledge lack, on the part of the physical coaches, regarding the periodizacion models, besides the disorganization in the planning of the training. Another evidenced point, it was the non use d and criteria to measure the load components, as volume and intensity.